The Influence Of Competence, Work Discipline, And Organizational Commitment On The Performance Of Civil Servants (ASN) In The Government Of North Bengkulu Regency (The Manager Review, 2025)
This study aims to analyze the influence of work ability, work discipline, and organizational commitment on the performance of State Civil Apparatus (ASN). This research employs a quantitative descriptive approach using a survey method. Data were collected through a questionnaire distributed to 315 ASN employees in North Bengkulu Regency. The data analysis methods used include descriptive analysis and multiple regression analysis. The results indicate that: (1) Work ability has a positive and significant effect on ASN performance in North Bengkulu, suggesting that ASN employees with higher work abilities tend to exhibit better performance; (2) Work discipline has a positive and significant impact on ASN performance in North Bengkulu, meaning that an increase in work discipline among ASN employees corresponds with improved performance; (3) Organizational commitment has a positive and significant effect on ASN performance in North Bengkulu, indicating that greater organizational commitment among ASN employees enhances their performance; and (4) Work ability, work discipline, and organizational commitment collectively have a significant effect on ASN performance in North Bengkulu. This implies that improvements in ASN work ability, work discipline, and organizational commitment will collectively enhance their performance.